KUALITAS AUDIT: SEBUAH META ANALISIS - Rifzita Vinda Arianiestasya; Ihyaul Ulum; A. Syaiful Hidayat Anwar (Universitas Muhammadiyah Malang, 2017)
This study aims to describe state of the art and measurement the audit quality from 1981 to2014. The research method used is meta-analysis and audit quality as the unit analysis in thisstudy. Data collection techniques with engineering documentation by gathers previous studiesabout audit quality.The result of this research shows that the study of audit quality began since 1981 and has beencontinued untill 2014. Meanwhile, indicator of audit quality measurement began with using thenumber of clients on research conducted by DeAngelo (1981). The initial period of the 1990’s byCopley (1991) using the measure indicators size of firm and fee audit. Subsequent developments carried out by Christiawan (2002) using measurement indicator of competence and independence. For measurement indicators most widely used is the size of KAP.Keywords: Audit Quality, Measurement Indicators, Meta Analysis, State of The Art